Autophagy Promotes Cigarette Smoke-Initiated and Elastin-Driven Bronchitis-Like Airway Inflammation in Mice - Huang, Hua-Qiong; Li, Na; Li, Dan-Yang; Jing, Du; Liu, Zheng-Yuan; Xu, Xu-Chen; Chen, Hai-Pin; Dong, Ling-Ling; Zhang, Min; Ying, Song-Min; Li, Wen; Shen, Hua-Hao; et al. (Frontiers in Immunology, 2021)
Cigarette smoke (CS)-induced macrophage activation and airway epithelial injury are both critical for the development of chronic obstructive pulmonary disease (COPD), while the eventual functions of autophagy in these processes remain controversial. We have recently developed a novel COPD mouse model which is based on the autoimmune response sensitized by CS and facilitated by elastin. In the current study, we therefore utilized this model to investigate the roles of autophagy in different stages of the development of bronchitis-like airway inflammation. Autophagic markers were increased in airway epithelium and lung tissues, and Becn+/- or Lc3b-/- mice exhibited reduced neutrophilic airway inflammation and mucus hyperproduction in this COPD mouse model. Moreover, treatment of an autophagic inhibitor 3-methyladenine (3-MA) either during CS-initiated sensitization or during elastin provocation significantly inhibited the bronchitis-like phenotypes in mice. Short CS exposure rapidly induced expression of matrix metallopeptidase 12 (MMP12) in alveolar macrophages, and treatment of doxycycline, a pan metalloproteinase inhibitor, during CS exposure effectively attenuated the ensuing elastin-induced airway inflammation in mice. CS extract triggered MMP12 expression in cultured macrophages, which was attenuated by autophagy impairment (Becn+/- or Lc3b-/-) or inhibition (3-MA or Spautin-1). These data, taken together, demonstrate that autophagy mediates both the CS-initiated MMP12 activation in macrophages and subsequent airway epithelial injury, eventually contributing to development COPD-like airway inflammation. This study reemphasizes that inhibition of autophagy as a novel therapeutic strategy for CS-induced COPD.